A Novel Evaluation Method of Hydrogen Production from Coal Based on AHP and GRA-TOPSIS - Shuheng Zhong; Kangdi Yang; Yongji Wang (Advances in Civil Engineering)
Coal is the cornerstone of China's energy. However, with the proposed goal of carbon peak and carbon-neutral in China, coal enterprises are in urgent need of exploring the path of transformation. Coal to hydrogen is an important way to achieve sustainable development of the coal industry. In this paper, four hydrogen production technologies, including coal gasification, coke oven gas, electrolytic water, and solar energy, are studied. A comprehensive evaluation model based on GRA-TOPSIS was constructed. The research shows that the coke oven gas is the most suitable hydrogen production technology for the transformation and development of coal enterprises. The evaluation model of hydrogen production technology in the transformation and development of coal enterprises constructed in this paper has a certain guiding effect on the technology selection of coal enterprises in the development of the hydrogen industry.